Influence of Size Company and the Company's Financial Performance Against the Value of Banking Listed In The Indonesia Stock Exchange Period 2013-2016 - Novia Leni Anjarsari, Anita Wijayanti & Endang Masitoh (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to know the influence of the size of the company and thefinancial performance of the company towards the banking companies listedon the Indonesia stock exchange period 2013 – 2016. The company'sfinancial performance measurement for researchers using the return on asset(ROA), whereas for the measurement of the value of the banking companyusing price to earnings ratio (PER). A sample of this company is a bankingcompany reported financial statements in successive – join in the period of2013 – 2016. The data were analyzed using SPSS 23.0. The results of thisresearch show that the size of the company doesn't have an effect on thevalue of the company. This indicates that the company is not his little biginfluence on the value of the company. While the company's financialperformance affects the value of banking companies. This indicates that thecompany's financial performance is good or bad can reflect the value of thecompany, the greater the financial performance of the company then thecompany value anyway.Keywords: financial performance, the value of the company, the size of the